SICKLE CELL DISEASE AND INFECTIONS IN HIGH- AND LOW-INCOME COUNTRIES - Giovanna Cannas (Mediterranean Journal of Hematology and Infectious Diseases)
Infections, especially pneumococcal septicemia, meningitis, and Salmonella osteomyelitis, are a major cause of morbidity and mortality in patients with sickle cell disease (SCD). SCD increased susceptibility to infection, while infection leads to SCD-specific pathophysiological changes. The risk of infectious complications is highest in children with a palpable spleen before 6 months of age. Functional splenectomy, the results of repeated splenic infarctions, appears to be an important host-defense defect. Infection is the leading cause of death, particularly in less developed countries. Defective host-defense mechanisms enhance the risk of pneumococcal complications. Susceptibility to Salmonella infections can be explained at least in part by a similar mechanism. In high-income countries, the efficacy of the pneumococcal vaccine has been demonstrated in this disease. A decreased in infection incidence has been noted in SCD patients treated prophylactically with daily oral penicillin. Studies in low-income countries suggest the involvement of a different spectrum of etiological agents.